Spatiotemporal Distribution Change of Online Reference During the Time of COVID-19. - Gerrish, Thomas; Kong, Ningning Nicole (Information Technology & Libraries, 2022)
The goal of this project was to identify the impact of the COVID-19 pandemic on the spatiotemporal distribution of the library's online patrons, so that we could assess if the scheduled library reference hours are meeting the needs of the academic community. We collected each online reference patron's location information via their IP address, as well as the timestamp of each online reference instance. The spatiotemporal distribution patterns were analyzed and compared before and after in-person instruction was suspended due to COVID-19 distance protocols and a closing of the campus in the 2020 spring semester. The results show that the geographic origins of reference questions redistributed after COVID-19 protocols were initially implemented and the university community underwent a temporary geographical redistribution. Reference question origins tended to move away from campus to other areas of the state, other states, and internationally. This population redistribution suggested that the library could adjust the online reference schedule to provide better access and service to patrons.